The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/ps.883
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance potential of fipronil in Musca domestica

Abstract: The toxicity of fipronil to insecticide-susceptible houseflies and the cross-resistance potential of fipronil were determined for six insecticide-resistant laboratory housefly strains by topical application and feeding bioassay. The insecticide-resistant strains represented different levels and patterns of resistance to pyrethroids, organophosphates, carbamates and organochlorines. Five strains were almost susceptible to fipronil in feeding bioassay with resistance factors at LC50 between 0.36 and 3.0. Four of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 33 publications
1
25
0
6
Order By: Relevance
“…Recently, there have been a few reports of C. suppressalis with low or middle level of resistance to fipronil in the field (Cao et al 2004; Jing et al 2005). In fact, high levels of fipronil resistance have been monitored in many other insects such as Plutella xylostella, Musca domestica, Oulema oryzae and Drosophila simulans (Sayyed et al 2004; Kristensen et al 2004; Ueno et al 2005). The mutation of Rdl genes was responsible for conferring high level of fipronil resistance in D. simulans (Goff et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been a few reports of C. suppressalis with low or middle level of resistance to fipronil in the field (Cao et al 2004; Jing et al 2005). In fact, high levels of fipronil resistance have been monitored in many other insects such as Plutella xylostella, Musca domestica, Oulema oryzae and Drosophila simulans (Sayyed et al 2004; Kristensen et al 2004; Ueno et al 2005). The mutation of Rdl genes was responsible for conferring high level of fipronil resistance in D. simulans (Goff et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the known tolerance of some insect predators to imidacloprid is advantageous concerning the safety of non-target organisms [37]. Fipronil, a broad spectrum phenylpyrazole, is highly toxic to dipterans including dairy populations of house flies [38], malarial and dengue mosquitoes [32], and fruit flies [39]. Although, fipronil will have a potential to control house flies in the future [38], baits containing fipronil should be evaluated at livestock farms under varying environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the increased frequency and years of use, fipronil resistance started to appear in insects 28,29 . Many studies reported fipronil re-sistance in various insect pests such as rice stem borer, house fly, and diamondback moth [29][30][31][32] . In this study we found that the average LC 50 values from toxicity tests of fipronil against RLF population collected from conventional paddy field was 63.3 ppm (Table 2), which is comparable to that of a previous study in Sri Lanka in 2001 that reported the LC 50 values of 60 ppm for the same insect and insecticide 33 .…”
Section: Toxicity Of Fipronil Against Rice Insect Pestmentioning
confidence: 99%